ANÁLISIS DE INDICADORES DE CONFIABILIDAD NIVEL 1 DEL SISTEMA ELÉCTRICO DE LA REGIÓN LITORAL DEL ECUADOR - REYES ULLÓN , JEAN CARLOS (2025)
This study addresses the energy crisis in the Coastal region of Ecuador, hypothesizing the existence of a structural insufficiency in the region's electrical system generation capacity